Growth and Yield Response of Detam 4 Soybean Variety on Single P Fertilizer and Vermicompost Application in Coastal Land - Cahyadi, Robi; Pujiwati, Hesti; Murcitro, Bambang Gonggo; Suprijono, Eko; Prameswari, Wuri (BPFP Universitas Bengkulu, 2024)
This research was conducted from July to November 2020 in the coastal lands of Ratu Agung District, Lempuing Village, Kuala Alam, Bengkulu City, at an elevation of 5 meters above sea level. The study aimed to investigate the interaction between vermicompost and single phosphorus (P) fertilizer on the growth and yield of Detam 4 soybean plants in coastal lands, focusing on determining the optimal doses for both inputs. The experiment was designed as a two-factor study using a factorial Randomized Complete Block Design (RCBD) with three replications. The first factor was vermicompost application at four levels: 0 tons ha-1, 5 tons ha-1, 10 tons ha-1, and 15 tons ha-1. The second factor was phosphorus application at three levels: 0 kg ha-1, 50 kg ha-1, and 100 kg ha-1. Observed variables included plant height, number of leaves, flowering age, number of productive branches, number of pods per plant, pod weight per plant, pod weight per plot, seed weight, and root weight. Data were analyzed using ANOVA at the 5% significance level, with a subsequent 5% LSD test if significant effects were found. The application of vermicompost at a dose of 10 tons ha-1 without the addition of single P fertilizer results in the best growth of the soybean variety Detam 4, characterized by the highest average shoot dry weight of 41.133 g, the fastest flowering age, and the greatest number of productive branches. The best yield of the Detam 4 soybean variety is achieved with the application of vermicompost at a dose of 15 tons ha-1, indicated by the highest number of productive branches and seed weight per plant. The independent application of single P fertilizer does not significantly enhance the growth and yield of the Detam 4 soybean variety in coastal land conditions.